توظيف الألعاب المحوسبة في تعلّم اللغة العربية وتعليمها لغير الناطقين بها للطلاب للمبتدئين في الجامعة الإسلامية العالمية بماليزيا أنموذجا - Sahrir, Muhammad Sabri; Mohamed Gameil Ali, Hussein (2011)

(untitled)
The process of teaching and learning vocabulary in Arabic language are still in the need of additional learning aids such as proper use of blackboards, flash cards, boards, language games, computer-assisted aids and so on. In this study, the researcher will present his experience in the design and development of computer games in the teaching and learning of Arabic language to non-native speakers among elementary students at International Islamic University Malaysia as a model. In fact, there are many studies and research conducted in educational computer games at the moment, particularly in the areas other than Arabic especially in Western countries. However, we find that the attention of scholars for this research in Malaysia is still at an early age, especially among researchers and teachers of Arabic. This is the main factor that prompted the researcher to conduct this study to look at the possibility of designing and utilizing computer games in the teaching and learning of Arabic language to non-native speakers at a pre-university level at International Islamic University Malaysia. The researcher has conducted the process of evaluating these games formatively throughout different classes in computer labs and classrooms. The researcher also collected the feedbacks from learners, teachers and experts pertaining to the implementation of this Arabic computer games by selecting the participants using purposive sampling method, by conducting formative evaluation in descriptive quantitative and qualitative research methods. The findings and results will be presented at the end of this paper, which consist of various degree of positive and negative feedbacks and responses, as well as suggestions for further improvement for the games in the future.